2002
DOI: 10.1182/blood.v99.5.1544
|View full text |Cite
|
Sign up to set email alerts
|

Severe deficiency of switched memory B cells (CD27+IgM−IgD−) in subgroups of patients with common variable immunodeficiency: a new approach to classify a heterogeneous disease

Abstract: Hypogammaglobulinemia is the hallmark of common variable immunodeficiency (CVID) syndrome, a heterogeneous disorder predisposing patients to recurrent bacterial infections. In this study, we investigated the peripheral B-cell compartment of 30 well-characterized CVID patients in comparison to 22 healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
473
8
31

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(538 citation statements)
references
References 49 publications
(60 reference statements)
26
473
8
31
Order By: Relevance
“…In addition to XLP, several other conditions are characterized by a deficiency of memory B cells and hypogammaglobulinemia, including CVID (20,22,43) and post-HSCT (25,44). Humoral immune responses are also reduced in neonates (45).…”
Section: Transitional B Cells Are Expanded In Humoral Immunodeficiencmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to XLP, several other conditions are characterized by a deficiency of memory B cells and hypogammaglobulinemia, including CVID (20,22,43) and post-HSCT (25,44). Humoral immune responses are also reduced in neonates (45).…”
Section: Transitional B Cells Are Expanded In Humoral Immunodeficiencmentioning
confidence: 99%
“…1a) (21,26). It was recently reported that some patients with CVID not only lacked memory B cells, but also B cells with an immature phenotype were occasionally detected (20). This prompted us to analyze the B cell compartment of XLP patients in greater detail to determine whether their CD27 Ϫ B cells were phenotypically similar to those in normal donors.…”
Section: Cd24 High Cd38 High B Cells Are Expanded In Xlpmentioning
confidence: 99%
“…Brouet et al [7] were the first to recognize the potential lack of B cells bearing CD27 in CVID, and this was amplified by Agematsu and Ochs [8]. Subsequently, the lack of switched memory B cells (B cells of the CD27 + , IgM-IgDphenotype) were characteristic of a large proportion of subjects with CVID, and that there relative lack of these cells could be used to divide patients into two clinically and immunologically different groups [3,9,10]. The lack of switched memory B cells was also found related to a lack of antibody production to pneumococcal vaccine, and interestingly, in these and other studies, also to the presence of autoimmune disease [11,12].…”
Section: Granulomatous Disease Autoimmunity and Memory B Cell Phenomentioning
confidence: 99%
“…Patients with common variable immunodeficiency (CVID), characterized by recurrent bacterial infections and a failure to make pneumococcal vaccination responses, were recruited as disease controls (n ϭ 28). All patients with CVID satisfied the Pan-American Group for Immunodeficiency and the European Society for Immunodeficiency diagnostic criteria for this condition (25,26). Twenty-five CVID patients were receiving IgG replacement containing exogenous pneumococcal and tetanus Abs.…”
Section: Controls and Patient Groupsmentioning
confidence: 99%